PENGHAPUSAN MEREK CRISTALINE (GIE CRISTALINE) OLEH PT. PEPPER TREE INVESTAMA BERDASARKAN UNDANG-UNDANG NO. 20 TAHUN 2016 - Manihuruk, Stephanie Karin; Saly, Jeane Neltje (Universitas Ekasakti, 2023)
Intellectual property rights are forms of human thought that are embodied in the form of works, works of art, designs and inventions that can be used in human life. The purpose of this study was to find out the lawsuit against the dispute over the brand mineral water product brand